FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TIMBULNYA GANGREN PADA PASIEN DIABETES MELLITUS DI RSUD K.R.M.T. WONGSONEGORO SEMARANG - Dela Rosa, Satya Kirana; Udiyono, Ari; Kusariana, Nissa; Saraswati, Lintang Dian (Jurnal Kesehatan Masyarakat (Undip), 2019)
Diabetes Mellitus is a disease which caused by pancreas that unable to produce enough insulin needed by the body. Without a good self-control, diabetes mellitus will cause complication in the form of the spring of gangrene. The complication prevalence of siabetical gangrene at RSUD K.R.M.T. Wongsonegoro tends to increased in the recent years. In 2017, the complication prevalence was 17,9%, while on January-March of 2018 it is increased to 19,2%. The purpose of this research is to analyze factors related to the spring of gangrene in diabetes mellitus’ patient at this hospital. This research is analytical research with case control study design. Samples of this resears was 70 patients which consists of 35 diabetes mellitus’ patients with gangrene complication and 35 diabetes mellitus’ patients without gangrene complication. Both samples are obtained by consecutive sampling method. Data analysis is conducted with chi-square test with 95 percents confident interval. The result of this research shows that there is a significant relation between the length of diabetes mellitus’ suffering (OR=4,333; 95%CI=1,569-11,967) and gangrene history (OR=9,203; 95%CI=2,675-31,661) with the spring of diabetical gangrene. In this research, we can conclude that the most dominant factor against diabetical gangrene’s complication is gangrene history. Based on this discovery, hopefully diabetes mellitus’ patients are willing to pay more attention to the usage of footwear to re-prevent the spring of gangrene wound.